JAPAN ARCHAEOLOGICAL REMAINS UTILIZATION PLAN - LITTLE TOKYO IN HALMAHERA DURING WORLD WAR II: English - Komang Ayu Suwindiatrini (Kalyanamitra: Journal of Archaeological Resource Management, 2025)
Kao, which used to be called Little Tokyo, was one of important base for Japanese. Kao was the main choice so it was used as the main base for the Japanese Navy in the Maluku Islands, also supported by the topography of the area which suited their war strategy. Using qualitative methods based on primary sources, reports from BPK Region XXI, results were obtained in identifying archaeological remains, not only on land but also at sea. Cultural Resource Management can be applied to this area. Through utilization efforts, it is hoped that it will have a positive impact on the surrounding community. Therefore, as a first step, a plan was made to utilize Japanese archaeological remains from World War II in Kao.